PENGARUH PENERAPAN MODEL OUTDOOR LEARNING TERHADAP KETERAMPILAN MENULIS PUISI SISWA KELAS III SEKOLAH DASAR - Mia Anjellina; Siti Halidjah; Tahmid Sabri (Universitas Tanjungpura, 2019)
AbstractThis study aimed to analyze the effect of the application of the outdoor learning model on poetry writing skills of class III Pontianak City 66 State Elementary School. The method used was the experimental method, while the form of research used was quasi experimental design with nonequivalent control group design. The study sample consisted of class III A as the experimental group and class III B as the control group selected by random sampling technique. The results of the t test are obtained by tcount 2.8255 and t table α = 5% (with dk = 32 + 29 - 2 = 59) of 2.0011, which means tcount (2.8255)> t table (2.0011), then the hypothesis alternative (Ha) is accepted. It can be concluded that there was an influence of the application of the outdoor learning model to poetry writing skills of class III students of Pontianak City 66 State Elementary School. From the results of the calculation of the effect size (ES) obtained by ES is 0.76 (medium criteria). This means that the application of the outdoor learning model has a good influence on poetry writing skills of class III students of Pontianak City 66 State Elementary School. Keywords: Outdoor learning, Poetry, Writing Skills